LRRK2 regulation of immune-pathways and inflammatory disease - Wallings, Rebecca L. (Biochem Soc Trans, 2019)
Mutations in the leucine-rich-repeat kinase 2 (LRRK2) gene are associated with familial and sporadic cases of Parkinson's disease but are also found in immune-related disorders such as inflammatory bowel disease, tuberculosis and leprosy. LRRK2 is highly expressed in immune cells and has been functionally linked to pathways pertinent to immune cell function, such as cytokine release, autophagy and phagocytosis. Here, we examine the current understanding of the role of LRRK2 kinase activity in pathway regulation in immune cells, drawing upon data from multiple diseases associated with LRRK2 to highlight the pleiotropic effects of LRRK2 in different cell types. We discuss the role of the bona fide LRRK2 substrate, Rab GTPases, in LRRK2 pathway regulation as well as downstream events in the autophagy and inflammatory pathways.